Mobile-Assisted Language Learning (MALL) for Academic Writing: A Thematic Analysis of Students’ Attitudes - Sahib, Nurfaizah; Maing, Rosmawati Abdul; Moelier, Dahlia D, (Ethical Lingua: Journal of Language Teaching and Literature, 2025)
This study explores students’ attitudes toward the use of Mobile-Assisted Language Learning (MALL) applications in academic writing classes at Universitas Bosowa. Specifically, it investigates how WhatsApp, Kahoot, and ChatGPT support students’ learning experiences within a constructivist framework. Employing a qualitative research design, data were collected through interviews and reflective journals. The data was analyzed using a thematic analysis approach. Findings reveal that students demonstrated positive attitudes toward MALL, particularly in terms of enhanced engagement, motivation, and collaborative learning. WhatsApp facilitated peer interaction and idea exchange, Kahoot increased classroom participation through gamification, and ChatGPT supported students in generating ideas and improving writing quality. Overall, the results indicate that integrating mobile applications fosters active participation and autonomy in academic writing, while also requiring careful guidance to balance benefits and challenges. This study suggests that lecturers should strategically integrate MALL tools to enhance academic writing, and further research should examine long-term impacts on writing development across diverse contexts.